Relation of the Segregative Origin of Chromosome Replication to the Origin of Replication After Amino Acid Starvation - Eberle, Helen (1969)
Cultures of Escherichia coli 15T(−) and K-12 were labeled with (3)H-thymine before, during, and after amino acid starvation. The number of labeled segregating units was measured by autoradiography of microcolonies derived from the labeled cells. In both strains, labels inserted before starvation and during starvation appeared to segregate as if incorporated into the same polynucleotide strands. However, labels inserted during and after starvation segregated as if incorporated into different polynucleotide strands. In view of previous data, it was concluded that replication after amino acid starvation originates from the region of the chromosome which serves as the origin for replication during normal growth and division.